Real Quality of Life vs Extended Representations of Your Own Clear Exterior - A. N. Tsatsulin (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2019)
The relevance. The article is devoted to the consideration of a question that would seem to be of a purely medical and philosophical nature, when a person, under aggressive influence and sophisticated pressure of the media, chooses a pattern of his eating behavior that differs markedly from the generally accepted behavior, called normal. Adhering to the chosen method of eating behavior, the consumer brings his body to a certain degree of weakening, mental torture and with a diagnosis of “Nervous orthorexia” turns into a patient of specialized rehabilitation clinics, becomes the ward of narrowly oriented doctors for the treatment of white brain. For any organism, the consequences of such a diagnosis are usually destructive.Objective. The authors of the article are trying to investigate the genesis of this little-studied problem and find any connection with the level and quality of life of Russians in recent years, with the quality of food consumed and with the general psychological state of society during its testing with an excessively long crisis.Methods. Diagnostic packages, testing of the functional state of patients according to Donini&Marsili, ORTO-15 and their clinical surveys are already as respondents. A large statistical sample of the online survey is represented by 612 respondents of different sexes and different age groups. To assess the standard of living and morbidity by Nervous orthorexia, statistical methods were used to measure the relationship of Spearman, Pearson, structural averages, etc.Results. Nervous orthorexia has been found to be characterized by the phenomenon of avoidant behavior that is included in the group of nonspecific eating disorders of the patient.Conclusion. The results of the retrospective period confirm the working hypothesis about the existence of a statistically significant relationship between the decline in the standard of living of urban population in the Northwestern Federal District and the incidence of Nervous orthorexia in its various manifestations.